TRANSFORMASI GOLONGAN ABANGAN MENUJU GERAKAN RADIKAL KEAGAMAAN (Dinamika Radikalisme Islam dalam Masyarakat Abangan di Solo, Jawa Tengah) - Yudi Setianto (Program Studi Sosiologi Agama Universitas Islam Negeri Sunan Kalijaga Yogyakarta, 2022)
From the New Order until now, Solo has a reputation as a base of religious radicalism. In fact, the people of Solo tend to abangan culture based on Javanese ethics rather than santri culture. In fact, Islamic radicalism can emerge and exist in this region. In addition, there was also a transformation of the abangan group into radical santri. For this reason, the purpose of this study is to analyze and describe in depth the emergence and existence of Islamic radicalism in abangan society, the transformation of the abangan group and thugs into radical santri. The type of research used is a qualitative method with a descriptive phenomenological approach. The results showed that the emergence of radical Islamic movements in Solo began during the New Order regime that was repressive towards itspeople. The presence of Ustaz Abdullah Sungkar and Abu Bakar Ba’asyir is a symbol of local resistance to the regime. Islamic radicalism in Solo is able to exist due to its supporters. Supporters of this movement are not limited to the santri group, but also the abangan group. The occurrence of this transformation is paradoxical, because the relationship between abangan and santri is dichotomous. In fact, there are groups of people who are interested in being part of radical students because of criticism of local politics.